Monetary policy rules: The market's view - Federico Di Pace; Giacomo Mangiante; Riccardo Masolo (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2024)
We study the market-perceived monetary policy rule of the Bank of England (BoE) using financial market data and macroeconomic surprises. Leveraging exogenous variations in inflation and industrial production (IP) surprises around Office for National Statistics releases, we estimate gilt yield responsiveness to inflation and real activity, revealing how markets expect the BoE to react to macroeconomic changes. Markets generally understand the UK flexible inflation-targeting regime, revising both inflation expectations and short-term rates upward after inflation surprises. We identify two key nonlinearities. First, perceived responsiveness changes over time, with short-term rates responding when away from their lower bound, and medium-term rates responding during periods of unconventional monetary policy. Second, financial markets expect a weaker response to inflation when it originates from supply shocks. This, however, does not translate into a risk of de-anchored expectations.
Keywords: C10; E50; E58; G10; 330; Market Perceptions; Financial Markets' expectations; Inflation; Yields; Monetary Policy Rule